USING MAX-PLUS ALGEBRA IN 2 SIGNALIZED CROSSROADS COORDINATION (Perner's Contacts, 2011)
The paper deals with the posibility of signalized crossroads coordination using Max-plus algebra. In the first part the problem is defined and a theoretical analysis of Max-plus algebra is given. In the next part of the paper the signalized crossroads coordination based on Max-plus algebra equations is developed. In the final part an evaluation is presented.